Information System Strategic Planning for M Group - Lily Damayanti; Teofilus Sunarsa; Yuki Gunawan (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2020)
M Group is a company engaged in the field of pharmacy, eye health and food. Along with the rapid growth of the company there are problems of how to make use the Information Technology department as optimal as possible and how to build a blue print of it strategy in handling a variety of issues and programs or initiatives to support the company's business strategy? This study aims to produce a strategic plan for information technology M Group. The research method used is John Ward and Joe Peppard’s framework for strategic planning of information technology and Scott A. Bernard’s Enterprise Architecture documentation. This study uses SWOT analysis, IT Balance Scorecard and Cost Benefit Analysis as a strategic tool to analyze the needs of Information System on M Group. After conducting the analysis then the Information System(IS) strategic planning is propose for M Group for next years (2020), which includes business strategies IS, IS / IT Management Strategy, Information System(IS) strategy and future application portfolio. The result of analysis and proposed strategies on M Group documented using the Enterprise Architecture Documentation.